Pengaruh Model Pembelajaran Berbasis Proyek (PjBL) terhadap Perilaku Prososial Siswa SD Kelas V di Surabaya - Prastyo, Danang; Sulistyowati, Ida; Budiyono, Sunu Catur (Universitas Nusantara PGRI Kediri, 2024)
The aim of the research is to determine the influence of prosocial behavior on Class V elementary school students in Surabaya through the PjBL Model. The population of public elementary school students and the sample are elementary school students in Class V A and B at Sumur Welut III Elementary School Surabaya. The data collection technique used the PTM (Prosocial Tendecies Measure) questionnaire adapted from Carlo. Data analysis uses the T-Test. The conclusion is that there is an influence of the PjBL Model on the prosocial behavior of class V students at SD Negeri Sumur Welut III Surabaya. The results of data processing show a sig (2-tailed) 0.00 < 0.05, value meaning that there is an influence of the PjBL Model on the prosocial behavior of class V students at SD Negeri Sumur Welut III Surabaya.